The Influence of the Pregnant Friend Application on Pregnant Women's Attitudes and Knowledge about Danger Signs of Pregnancy at RSIA Masyita - Syarif, Sutrani; Eryanti Kusniyanto, Rahayu; Darman, Amriani (Journal of Midwifery, 2024)
Background: Every pregnancy carries the risk of mild or severe complications that cause death, morbidity, disability in the mother or baby. Attitudes and knowledge about the danger signs of pregnancy are very important to prevent unwanted complications during pregnancy. Efforts to increase knowledge and attitudes about the danger signs of pregnancy are very necessary. The pregnant friend application is a health application for pregnant women as a means of communicating between pregnant women and midwives to gain knowledge and convey complaints about pregnancy directly. Objective: to determine the effect of using the "Pregnant Friends" application on attitudes and knowledge about the danger signs of pregnancy at RSIA Masyita. Method: This study used a one group pretest-posttest design, the sample in this study was 30 pregnant women visiting RSIA Masyita, the research was conducted in June-August 2023. Data were analyzed using the Wilcoxon test. Results: After carrying out the Wilcoxon test, the value obtained was p = 0.001 for the Knowledge variable and for the attitude variable, the value obtained was p = 0.004 (p